2018
DOI: 10.1098/rsbl.2018.0090
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the bird's beak: new insights from dinosaur incubation periods

Abstract: The toothless beak of modern birds was considered as an adaption for feeding ecology; however, several recent studies suggested that developmental factors are also responsible for the toothless beak. Neontological and palaeontological studies have progressively uncovered how birds evolved toothless beaks and suggested that the multiple occurrences of complete edentulism in non-avian dinosaurs were the result of selection for specialized diets. Although developmental biology and ecological factors are not mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The lack of complexed enamel in most Cretaceous birds suggests their substantially weakened role in resisting wear during food processing. The simplified and thin enamel layer may also be related to a fast incubation time and a lack of adequate time for mineral deposition [30,31]. In comparison to the commonly reported paralleled enamel found in dromaeosaurids [32], even enantiornithines with relatively thick enamel show a simplified crystal structure without a clearly layered structure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The lack of complexed enamel in most Cretaceous birds suggests their substantially weakened role in resisting wear during food processing. The simplified and thin enamel layer may also be related to a fast incubation time and a lack of adequate time for mineral deposition [30,31]. In comparison to the commonly reported paralleled enamel found in dromaeosaurids [32], even enantiornithines with relatively thick enamel show a simplified crystal structure without a clearly layered structure.…”
Section: Discussionmentioning
confidence: 95%
“…In the face of intensified competition from carnivorous theropods and pterosaurs, changes of feeding ecology to a more herbivorous diet could be one of the major selective factors ruling on the evolution of Cretaceous stem birds, as exemplified by tooth changes in both exterior morphology and internal microstructures. In addition to feeding adaptation, a recently hypothesized developmental process (i.e., incubation duration) may also have constrained tooth growth [30]. Fast embryonic growth and a shortened incubation time may have restricted tooth development compared with non-avian theropods with a longer period of incubation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Functional morphology. Tooth loss and edentulism in theropods have been recently investigated by Zhou and Li (2009), Davit-Béal et al (2009), Louchart and Viriot (2011), Zanno and Makovicky (2011), Lautenschlager et al (2013), Meredith et al (2014), Bhullar et al (2016), Wang et al (2017b), Erickson et al (2017) and Yang and Sander (2018). The classical reasons for the origin of edentulism are related to developmental economy and for food acquisition.…”
Section: Partial and Complete Edentulismmentioning
confidence: 99%
“…It is noteworthy that this approach could be tested on other dinosaurs closer to the bird lineage (e.g., Torvosaurus; Araújo et al, 2013). Yang and Sander (2018) suggested that the incubation period is a selection factor for edentulism or, in other words, the selection for tooth loss was a side effect of the selection for fast embryo growth and thus shorter incubation. This hypothesis, however, lacks the support of experimental evidence.…”
Section: Partial and Complete Edentulismmentioning
confidence: 99%
“…Regarding the reduction or loss of the teeth of birds, it is traditionally attributed to lightening the body for flight (Zhou et al 2010;Zheng et al 2011). This, however, cannot explain the occurrence of numerous toothed Mesozoic birds (e.g., Enantiornithes and Ichthyornis) (Zhou et al 2010;Yang and Sander 2018; O'Connor 2019), and hence teeth were probably not a limiting factor for flight (O'Connor and Zhou 2015; Chiappe and Qingjin 2016;Mayr 2017;Zhou et al 2019). Alternatively, teeth reduction or loss is considered to be partly due to the functional replacement by the muscular gizzard (Louchart and Viriot 2011;Zheng et al 2014;O'Connor 2019).…”
Section: Specialized Digestive System Of Birds Responsive To Predatiomentioning
confidence: 99%